Fineness of grain and the hylomorphism of experience - Settegast, Sascha (Synthese, 2023)
A central objection to McDowell’s conceptualism about empirical content concerns the fine-grained phenomenology of experience, which supposedly entails that the actual content of experience cannot be matched in its particularity by our concepts. While McDowell himself has answered this objection in recourse to the possibility of demonstrative concepts, his reply has engendered a plethora of further objections and is widely considered inadequate. I believe that McDowell’s critics underestimate the true force of his reply because they tend to read unrecognized empiricist presuppositions into his account of experience. To show this, I introduce a new hylomorphic reading of McDowell’s account of experience and argue that the objections to his reply all rest on a specific empiricist assumption, which is untenable because it conflates the form of experience with its content. Consequently, conceptualism so understood can resist all of these objections, as I attempt to show by systematizing and answering them.